2006
DOI: 10.1038/modpathol.3800484
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 protein expression is a negative prognostic marker in breast carcinoma

Abstract: The protein encoded by the MDM2 oncogene inhibits the function of p53, leading to increased cell growth, avoidance of apoptosis, tolerance of genetic instability, and resistance to chemotherapy. The present study was performed to evaluate the relationship between MDM2 protein expression and survival in breast carcinoma. Two series of cases were used in this study: the first to identify the cutoff to be used in the interpretation of MDM2 immunostaining and perform preliminary survival analysis, and a second, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…In breast cancer expression of MDM2 at protein level is related to survival [37]. Our results clearly demonstrate a relation between amplification of 12q and poor prognosis in breast cancer although no genes fulfill criteria for additional regulation.…”
Section: Candidate Genesmentioning
confidence: 65%
“…In breast cancer expression of MDM2 at protein level is related to survival [37]. Our results clearly demonstrate a relation between amplification of 12q and poor prognosis in breast cancer although no genes fulfill criteria for additional regulation.…”
Section: Candidate Genesmentioning
confidence: 65%
“…This suggests the intriguing possibility that triple negative breast carcinomas may derive from early stage ERa þ tumors that development of centrosome amplification due to abrogated of p53 function. In addition, vMCF-7 DNP53 xenografts overexpress the oncoprotein Mdm2, which has been demonstrated to induce ER degradation and is associated with an aggressive phenotype (Kinyamu and Archer, 2003;Turbin et al, 2006). A recent study by Duong et al (2007) demonstrated that Mdm2 ubiquitin ligase activity degrades the ERa protein and thus downregulates ERa expression.…”
Section: Discussionmentioning
confidence: 99%
“…A T-to-G substitution in this region increases the binding affinity of the transcriptional activator Sp1, which results in high levels of MDM2 RNA and protein (24,29). The heightened MDM2 levels are poor prognostic factors in many human cancers, including lung cancers and breast cancers (30,31). MDM2 is a key negative regulator of p53, the most important tumor suppressor (32,33), which targets p53 for proteosomal degradation (33 -35).…”
Section: Discussionmentioning
confidence: 99%